KUALITAS PELAYANAN, KUALITAS PRODUK, DAN HARGA SEBAGAI PENENTU KEPUASAN KONSUMEN TOKO ONLINE HNA SHOP SURAKARTA - Basuki Sri Rahayu; Abdurrohman Hasyir (STIE St. Pignatelli Surakarta, 2022)
The purpose of this study is to determine, analyze, and provide empirical evidence of the influence of service quality, product quality, and price on consumer satisfaction at the HNA Shop online store. This study uses a primary data collection method, namely by distributing questionnaires where the population in this study are consumers of the HNA Shop Online Store. Sampling in this study used a simple random sampling technique with a sample of 100 respondents. The analysis technique used is validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear regression test, t test, F test, and coefficient of determination test. The results of the validity and reliability testing showed that all of the questions asked were valid and reliable. The results of the multiple linear regression equation variables of service quality, product quality, and price have a positive effect on customer satisfaction. The results of the t- test indicate that the variables of service quality, product quality, and price partially have a significant effect on consumer satisfaction. The results of the F test show that service quality, product quality, and price simultaneously have a significant effect on customer satisfaction. The results of the coefficient of determination test (R2) show that the Adjusted R Square value is 0.467, which means that service quality, product quality, and price can affect customer satisfaction by 46.7% and the remaining 53.3% is influenced by other variables outside of this study. For example promotion, location, brand image and others.